Decomposing significant factors of Coulomb stress and its components in injection-induced seismicity - Yao Zhang; Qi Li; Yongsheng Tan; Xiaying Li; Yiyan Zhong (Journal of Rock Mechanics and Geotechnical Engineering)
Injection-induced seismicity has been a focus of industry for decades as it poses great challenges to the associated risk mitigation and hazard assessment. The response surface methodology is integrated into the geo-mechanical model to analyze the effects of multiple factors on induced seismicity during the post shut-in period. We investigate the roles of poroelastic stress and pore pressure diffusion and examine the differences in the controlling mechanism between fault damage zones and the fault core. A sensitivity analysis is conducted to rank the selected factors, followed by a Box‒Behnken design to form response surfaces and formulate prediction models for the Coulomb stress and its components. Reservoir properties significantly affect the potentials of induced seismicity in the fault by changing pore pressure diffusion, which can be influenced by other factors to varying degrees. Coulomb stress is greater in pressurized damage zones than in fault cores, and the seismicity rate exhibits a consistent variation. Poroelastic stress plays a similar role to pore pressure diffusion in the stability of the fault within the pressurized damage zones. However, pore pressure diffusion dominates in the fault core due to the low rigidity, which limits the accumulation of elastic energy caused by poroelastic coupling. The slip along the fault core is a critical issue to consider. The potential for induced seismicity is reduced in the right damage zones as the pore pressure diffusion is blocked by the low-permeability fault core. However, poroelastic stressing still occurs, and in deep basements, the poroelastic effect is dominant even without a direct increase in pore pressure. The findings in this study reveal the fundamental mechanisms behind injection-induced seismicity and provide guidance for optimizing injection schemes in specific situations.